Analisis Faktor Permintaan Non Fungsional Kelompok Non-Member Terhadap Permintaan (Seri 2) - Iskandar Putong (Binus Business Review, 2011)
Factor analysis of non functional Demand Non-Member On to Demand aimed to discover whether there is significant influence of non-functional variable on demand. Three independent variables (the effect), ie, X1 for Snob Effect (Mode), X2 for the Bandwagon effect (Prestige) and X3 for the Veblen Effect (Show-off) and 1 dependent variable Y for Demand. The number of respondents of 50 and 22 indicators is statistically valid. Analysis tool using the Model Correlation and simple Regression (Simple/Bivariate), Correlation and Regression Simultaneously (Multiple) Regression and Partial Correlation. The results of analysis proved statistically with LOC of 95%, indicating that the bivariate, partial unison and Simultaneously there is positive and significant correlation between variables X to Y, except for variable X2 (Prestige) on Bivariate correlation.